Islamic college students’ gratitude model: The role of social support in mediating spiritual well-being - Tamami, Abi Syamsudin; Hidayati, Fina; Nuqul, Fathul Lubabin (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2025)
Islamic college students are individuals who simultaneously study at a university and an Islamic boarding school (pesantren), thus facing complex academic, social, and religious pressures. This study tested a gratitude model by examining the role of social support in gratitude through the mediation of spiritual well-being. A total of 233 Islamic college students from various Islamic boarding schools in Indonesia participated through an online survey using a purposive sampling technique. Structural Equation Modeling (AMOS 26) analysis showed that social support had a positive effect on spiritual well-being (β = 0.314; p < 0.001), but did not have a direct effect on gratitude (β = –0.010; p = 0.815). In contrast, spiritual well-being had a strong influence on gratitude (β = 0.713; p < 0.001) and fully mediated the relationship between the two (β = 0.224; p < 0.001), with a marginal model fit (χ²/df = 2.98; RMSEA = 0.094). These results indicated that gratitude is not formed directly from social support, but instead through spiritual well-being, which transforms external influences into inner well-being and grateful behavior. These findings extended the broaden-and-build theory (Fredrickson, 2004) from an Islamic psychology perspective and provide a practical basis for developing spiritual interventions to strengthen the psychological resilience of Islamic college students.